Penyediaan Fasilitas Hunian di Perumahan KORPRI Salatiga: Realita dan Konsep Neighborhood Unit - S Sunarti; Nany Yuliastuti; Wido Prananing Tyas; Dwi Putri Puspa Sari (Diponegoro University, 2020)
KORPRI housing in Salatiga City is one form of providing low-cost housing to overcome the backlog problem for civil servants who do not yet have a home. Since it was built in 2014, until now not 100% development has been realized, especially in the provision of residential facilities. It is important for an environment to be able to provide services and provide adequate facilities to meet the needs for the survival of the occupants. This study aims to examine the physical environment of housing based on the provision of facilities in KORPRI housing, Praja Mulia, in the perspective of a neighborhood unit as a physical structuring concept of an ideal residential environment. The method used is quantitative by using descriptive analysis techniques. Primary data collection techniques are carried out by means of observation and interpretation of images, secondary data derived from documents and literature studies related to KORPRI housing development. The results showed that based on the concept of neighborhood units, as cheap housing, Praja Mulia Housing with a planned population of 1,380 inhabitants had non-ideal neighborhood unit facilities. The existing facilities are only open spaces in 3 locations (3% of the total housing area) and other public facilities that are still planned. Novelti of this research housing for civil servants do not use environmental unit theory but only pay attention to the house as objects (nouns) used for investment and commodity. This condition creates a burden and becomes a challenge for the city and the surrounding area in providing facilities and services for residents who are not served in their neighborhood units.